Tinjauan Hukum Pidana Islam Terhadap Pasal 274 Undang-Undang Nomor 1 Tahun 2023 tentang Penyelenggaraan Pesta atau Keramaian - Khairi Akbar, Ahmad; Rizal, Muhammad (UNES Law Review, 2024)
This research aims to examine the rules and sanctions in Islamic criminal law concerning Article 274 of Law No. 1 of 2023 on the organization of parties or festivities. The study was conducted using qualitative research methods, specifically normative juridical research, supplemented with literature review. Based on the research findings, it is evident that the use of road functions beyond their intended purposes is regulated under Article 1, number 9 of Perkapolri 10/2012. Personal use of these roads is also addressed in Article 16, paragraph 2 of Perkapolri 10/2012, Article 127, paragraph 3 of the Traffic and Road Transportation Law (UU LLAJ), and Article 15, paragraph 2 of Perkapolri 10/2012. If the use of the road for personal purposes results in road closure, permission must be obtained if alternative routes are available, as stipulated in Article 128, paragraph 1 of UU LLAJ and Article 15, paragraph 3 of Perkapolri 10/2012. Such changes must be accompanied by emergency traffic signs in accordance with Article 128, paragraph 2 of UU LLAJ and Article 15, paragraph 4 of Perkapolri 10/2012. Additionally, individuals who use road functions beyond their intended purposes for personal gain may be subject to sanctions under the applicable provisions of the Criminal Code (KUHP).